DIALECTICS OF SCIENTIFIC KNOWLEDGE AND ACTIVITY IN RELATION TO THE DEVELOPMENT OF POSTNONCLASSICAL SCIENCE: RESEARCH DIRECTIONS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article analyzes how the dialectical connection between scientific knowledge and activity acquires new meaning in the context of postnonclassical science. Since the second half of the twentieth century, the postnonclassical stage of scientific development has promoted approaches based on the complex interaction between the knowing subject and the known object. On this basis, the article highlights the contextual, systemic, and self-organizing characteristics of knowledge activity. It also examines the philosophical methodology of scientific cognition, the role of human practical activity, and the socio-cultural factors that arise during the process of knowing, thereby demonstrating that scientific cognition includes not only theoretical but also activity-oriented forms.